The development of HPLC-DAD method for determination of active pharmaceutical ingredient in the potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio) acetate substance - Shcherbyna Roman (Current Issues in Pharmacy and Medical Sciences, 2019)
Derivatives of 1,2,4-triazole are actively researched by scientists and synthetic pharmacologists. The last studies have shown that potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate with low toxicity series exhibits antioxidant and hepatoprotective properties. Therefore, the purpose of this work was to develop a method for determining the API in the potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate substance using the method of high-performance liquid chromatography with diode array detection (HPLC-DAD). As a result of this work, it is shown that the developed method is specific and meets the requirements of linearity, accuracy and precision. The results of determining the contents of the API in real samples indicate that the method can be proposed to control the quality of the potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate substance.